N-Doped carbon as a solid base catalyst for continuous flow Knoevenagel condensation. Issue 7 (6th May 2021) - Brzęczek-Szafran, Alina; Gwóźdź, Magdalena; Kolanowska, Anna; Krzywiecki, Maciej; Latos, Piotr; Chrobok, Anna
Abstract : A stability survey of a basic N-doped carbon catalyst in a continuous flow process together with a study of process parameters affecting the batch system and their correlation to the flow protocol is described. Abstract : The application of N-doped carbon as a basic, heterogeneous catalyst in a continuous-flow process is described for the first time. The Knoevenagel condensation reaction was chosen to demonstrate the potential of N-doped carbon toward the development of sustainable, scalable processes that require a basic catalyst. The practical potential and performance advantages of the flow approach compared to a conventional batch system were envisioned. Under flow conditions, products were continuously synthesized for 200 h with high conversions up to 95%. The presented metal-free flow system successfully operated under mild reaction conditions, with temperatures ranging from 25 to 70 °C and ethanol as a solvent, which embody key principles of green chemistry.